Whole exome sequencing of biliary tubulopapillary neoplasms reveals common mutations in chromatin remodeling genes - Groß, Claudia; Engleitner, Thomas; Lange, Sebastian; Weber, Julia; Jesinghaus, Moritz; Konukiewitz, Björn; Muckenhuber, Alexander; Steiger, Katja; Pfarr, Nicole; Goeppert, Benjamin; Keller, Gisela; Weichert, Wilko; et al. (Cancers, 2021)
The molecular carcinogenesis of intraductal tubulopapillary neoplasms (ITPN), recently described as rare neoplasms in the pancreato-biliary tract with a favorable prognosis despite a high incidence of associated pancreato-biliary adenocarcinoma, is still poorly understood. To identify driver genes, chromosomal gains and losses, mutational signatures, key signaling pathways, and potential therapeutic targets, the molecular profile of 11 biliary and 6 pancreatic ITPNs, associated with invasive adenocarcinoma in 14/17 cases, are studied by whole exome sequencing (WES). The WES of 17 ITPNs reveals common copy number variants (CNVs) broadly distributed across the genome, with recurrent chromosomal deletions primarily in 1p36 and 9p21 affecting the tumor suppressors CHD5 and CDKN2A, respectively, and gains in 1q affecting the prominent oncogene AKT3. The identified somatic nucleotide variants (SNVs) involve few core signaling pathways despite high genetic heterogeneity with diverse mutational spectra: Chromatin remodeling, the cell cycle, and DNA damage/repair. An OncoKB search identifies putative actionable genomic targets in 35% of the cases (6/17), including recurrent missense mutations of the FGFR2 gene in biliary ITPNs (2/11, 18%). Our results show that somatic SNV in classical cancer genes, typically associated with pancreato-biliary carcinogenesis, were absent (KRAS, IDH1/2, GNAS, and others) to rare (TP53 and SMAD4, 6%, respectively) in ITPNs. Mutational signature pattern analysis reveals a predominance of an age-related pattern. Our findings highlight that biliary ITPN and classical cholangiocarcinoma display commonalities, in particular mutations in genes of the chromatin remodeling pathway, and appear, therefore, more closely related than pancreatic ITPN and classical pancreatic ductal adenocarcinoma.
Gesehen am 06.08.2021